Lagrangian Dual Decomposition for Joint Resource Allocation Optimization Problem in OFDMA Downlink Networks. (30th October 2018) - Jia, Li-Jun; He, Yu-Cheng; Chen, Dong-Hua; Zhou, Lin
Abstract : This paper proposes an efficient method for joint power and subcarrier allocation in a multicell multiuser OFDMA downlink network. The joint optimization problem is formulated with the objective of maximizing the energy efficiency subject to the constraints on the quality of service in sum transmission rates for each cell and the total transmit power for the network. Due to intercell cochannel interferences and multiple variable coupling, the problem is intractable in its original form. To relax the difficulties in coordinating cochannel interferences, we introduce the tolerable interferences constraints for interference channels. To cope with the multiple variable coupling, we decompose the joint optimization problem into two iterative processes of user scheduling and a parametric convex optimization problem, where the energy efficiency is treated as the parameter and approached by bisection search. Then, by double dual decomposition, the parametric convex problem is transformed into Lagrangian dual problems at two levels of cells and subcarriers, and a decentralized solution is obtained in closed form. Based on the reformulations, an iterative subgradient algorithm is presented for approaching the joint optimization problem with acceptable complexity. Computer simulations are conducted to validate the proposed algorithm and examine the effects of various system parameters.